The interpretative significance of ripple-derived sedimentary structures within an upper Neogene fluvial succession of central Poland - Maciaszek, Piotr; Chomiak, Lilianna; Wachocki, Robert; Widera, Marek (Geologos, 2019)
Sedimentary structures discussed in the present study are genetically linked to ripples that consist of pure sand or alternating sand and mud layers. All types of ripple-related structures, such as climbing-ripple cross-lamination and heterolithic bedding, i.e., flaser, wavy and lenticular (nodular), have been identified for the first time in fluvial strata that have been characterised previously as commonly massive. These small-scale bedforms, produced by migrating ripples, have been documented in a fluvial channel of late Neogene age in central Poland. The abundance and co-occurrence of the structures discussed and their spatial distribution provide evidence of their formation under very low-energy conditions, when flow velocity changed markedly, but was often significantly less than 0.5 m/s. Therefore, these ripple-derived sedimentary structures are here recognised as typical of channel fills of an anastomosing river.